2014
DOI: 10.1177/0956462414552696
|View full text |Cite
|
Sign up to set email alerts
|

Operations research study to implement HIV and syphilis point-of-care tests and assess client perceptions in a marginalised area of Lima, Peru

Abstract: In Peru, a significant proportion of people tested for HIV and syphilis do not receive timely results. Our objective was to assess the institutional feasibility of implementing simultaneous HIV/syphilis point-of-care tests (POCTs) and client perceptions regarding these POCTs. POCTs were implemented in a hospital consultation room in a marginalized zone of Lima. A time-series design was used to compare the proportion of tested clients who received timely results, with and without the POCT intervention. Experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Dual point-of-care tests for HIV and syphilis, which meet the WHO ASSURED criteria of being Affordable, Sensitive, Specific, User-friendly, Rapid and robust, Equipment free, and Deliverable to those who need them, are now available [24]. Replacement of individual HIV and syphilis tests with these dual tests has occurred in some countries in South America [25] and will facilitate the integration of programs for PMTCT of HIV and syphilis, ensuring that all women screened for HIV are also screened for syphilis. …”
Section: Discussionmentioning
confidence: 99%
“…Dual point-of-care tests for HIV and syphilis, which meet the WHO ASSURED criteria of being Affordable, Sensitive, Specific, User-friendly, Rapid and robust, Equipment free, and Deliverable to those who need them, are now available [24]. Replacement of individual HIV and syphilis tests with these dual tests has occurred in some countries in South America [25] and will facilitate the integration of programs for PMTCT of HIV and syphilis, ensuring that all women screened for HIV are also screened for syphilis. …”
Section: Discussionmentioning
confidence: 99%
“…31 Studies have suggested that rapid HIV testing can increase HIV testing uptake, maternal HIV care, and uptake of ART. 32,33 The effect of rapid HIV testing on maternal linkage to HIV care was found in a systematic review and meta-analysis by Mashamba-Thompson et al 32 The availability of rapid tests for HIV including self HIV testing technologies has increased in LMICs. 3339 Studies have demonstrated their acceptability and usefulness by increasing the proportion of pregnant women who are tested during ANC and provided same-day testing and treatment.…”
Section: Availability Of Poc Testing For Pmtct In Lmicsmentioning
confidence: 99%
“…32,33 The effect of rapid HIV testing on maternal linkage to HIV care was found in a systematic review and meta-analysis by Mashamba-Thompson et al 32 The availability of rapid tests for HIV including self HIV testing technologies has increased in LMICs. 3339 Studies have demonstrated their acceptability and usefulness by increasing the proportion of pregnant women who are tested during ANC and provided same-day testing and treatment. 33,34,39 Point-of-care HIV testing during time of labor and delivery offers the last opportunity for PMTCT in settings where women do not receive adequate ANC.…”
Section: Availability Of Poc Testing For Pmtct In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…POCT is generally well accepted by clients and health professionals to diagnose either HIV or syphilis, as demonstrated in Lima, Peru [57]; Manaus, Brazil [56]; India [40]; Kenya [58]; Tanzania [49,59]; China; Uganda; Zambia [49]; Canada [27]; and England [54]. Clients were satisfied in receiving the test results rapidly in the first visit [24,49], with no need to come back for results.…”
Section: Impact Of Tests' Introductionmentioning
confidence: 99%